2018
DOI: 10.1002/rmv.2023
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of ganciclovir pharmacodynamics during the prevention of cytomegalovirus infection in adult solid organ transplant recipients

Abstract: Summary Human cytomegalovirus (CMV) represents the most common infection among recipients of solid organ transplants (SOTs). Previous meta‐analysis showed 0.8% of SOT recipients developed CMV disease whilst receiving valganciclovir (ValGCV) prophylaxis. However, the clinical utility of monitoring ganciclovir (GCV) blood concentrations is unclear. We systematically reviewed the association between GCV concentrations during prophylaxis and the incidence of CMV. MEDLINE and EMBASE databases were searched for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(143 reference statements)
0
6
2
2
Order By: Relevance
“…The recommended dose of ganciclovir in children at 5 mg/kg every 12 hours has been extrapolated primarily from adult studies, with only small cohort studies completed in children. 2 These studies evaluated paediatric patients with very select disease processes and may not represent real-world patient care situations. Additionally, inter-patient variability in children is well-documented with potential underdosing in children compared to adults.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…The recommended dose of ganciclovir in children at 5 mg/kg every 12 hours has been extrapolated primarily from adult studies, with only small cohort studies completed in children. 2 These studies evaluated paediatric patients with very select disease processes and may not represent real-world patient care situations. Additionally, inter-patient variability in children is well-documented with potential underdosing in children compared to adults.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…However, despite the diagnostic and therapeutic solutions in the form of antiviral drugs, the hCMV is still a significant cause of organ infections (most often: pneumonia, liver, retina, and intestinal diseases) as well as systemic disorder. It is also one of the most important viruses associated with the post-transplantation complications, transplant failure, as well as deaths among recipients of allogeneic hematopoietic cells (allo-HCT) and organs [1,5,19,30,35,39].…”
Section: Introduction -Epidemiology Of Hcmv Infections and Prophylaximentioning
confidence: 99%
“…This is mainly used among patients who are at a very high risk of developing a disease caused by the CMV infection. The use of chemoprophylaxis allows the reduction of morbidity and mortality as a result of cytomegalovirus infection, especially among patients after hematopoietic cell transplantation [2,5,12,19,20,39].…”
Section: Introduction -Epidemiology Of Hcmv Infections and Prophylaximentioning
confidence: 99%
“…The pharmacokinetics (PK) of GCV are highly variable after VGCV administration; therefore, it is difficult to achieve GCV exposure within a therapeutic range after a standard dosing regimen 14 . Therapeutic drug monitoring (TDM) is suggested to be useful in individualized therapy 15–18 . In a previous study conducted in a group of 240 high‐risk transplantation patients, it was suggested that the monitoring of GCV exposure in both adult and pediatric solid‐organ transplantation patients receiving VGCV therapy is helpful.…”
mentioning
confidence: 99%
“…14 Therapeutic drug monitoring (TDM) is suggested to be useful in individualized therapy. [15][16][17][18] In a previous study conducted in a group of 240 high-risk transplantation patients, it was suggested that the monitoring of GCV exposure in both adult and pediatric solid-organ transplantation patients receiving VGCV therapy is helpful. The area under the concentration time curve (AUC) in the range of 40-50 μgh/mL in patients after a once-daily dose at steady state predicted a low incidence of breakthrough viremia during prophylaxis.…”
mentioning
confidence: 99%